Testicular cancer incidence predictions in Europe 2010–2035: A rising burden despite population ageing. Issue 3 (28th December 2019) - Znaor, Ariana; Skakkebæk, Niels E.; Rajpert‐De Meyts, Ewa; Laversanne, Mathieu; Kuliš, Tomislav; Gurney, Jason; Sarfati, Diana; McGlynn, Katherine A.; Bray, Freddie
Abstract : Testicular cancer is the most common cancer among young men of European ancestry, with about one‐third of all cases occurring in Europe. With the historically increasing trends in some high‐incidence populations reported to have stabilised in recent years, we aimed to assess recent trends and predict the future testicular cancer incidence burden across Europe. We extracted testicular cancer (ICD‐10 C62) incidence data from Cancer Incidence in Five Continents Volumes VII–XI and complemented this with data published by registries from 28 European countries. We predicted cancer incidence rates and the number of incident cases in Europe in the year 2035 using the NORDPRED age‐period‐cohort model. Testicular cancer incidence rates will increase in 21 out of 28 countries over the period 2010–2035, with trends attenuating in the high‐incidence populations of Denmark, Norway, Switzerland and Austria. Although population ageing would be expected to reduce the number of cases, this demographic effect is outweighed by increasing risk, leading to an overall increase in the number of cases by 2035 in Europe, and by region (21, 13 and 32% in Northern, Western and Eastern Europe, respectively). Declines are however predicted in Italy and Spain, amounting to 12% less cases in 2035 in Southern Europe overall. In conclusion, the burden of testicular cancer incidence in Europe will continue to increase, particularly in historically lower‐risk countries. The largest increase in the number of testicular cancer patients is predicted in Eastern Europe, where survival is lower, reinforcing the need to ensure the provision of effective treatment across Europe. Abstract : What's new? Testicular cancer (TC) is the most common cancer among young men of European ancestry. As the population ages, will rates of TC decrease? In this study, the authors found that, on the contrary, TC risk is predicted to rise in many European countries through the year 2035. The largest increase in the number of TC patients (32%) is predicted in Eastern Europe, where survival is also lower. These results reinforce the need to ensure that effective treatment is provided throughout Europe.